Implementasi Manajemen Kinerja Pendidik dalam Meningkatkan Kualitas Pembelajaran Siswa - Ahmad Sofiyudin; Abdullah Aminuddin Aziz (Insan Zenius Ilmiah, 2025)
This research is motivated by the implementation of structured and highly disciplined teaching staff management at SMP A. Wahid Hasyim Tebuireng, which focuses on improving the quality of learning through teaching staff personnel management. The objectives of this study are: (1) to determine the performance management of teachers, (2) to determine the quality of student learning, and (3) to analyze the implementation of teaching staff performance in improving the quality of student learning at SMP A. Wahid Hasyim Tebuireng. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. Data analysis is carried out through data processing, categorization, and interpretation. The results of the study indicate that management has an important role in the education system because it is able to optimize human resources in a directed manner to achieve institutional goals. Based on GR Terry's theory, management functions include planning, organizing, implementing, and supervising. The implementation of these four functions at SMP A. Wahid Hasyim is running well and has a positive impact on improving the quality of learning. However, it was found that the madrasah still needs to optimize training and guidance related to the use of learning technology, especially in the preparation of lesson plans, syllabi, teaching methods, and teaching materials to support the effectiveness of the learning process.